Multisensory feature integration in (and out) of the focus of spatial attention - Spence, C; Frings, C (Springer, 2019)
Anne Treisman transformed the way in which we think about visual feature integration. However, that does not mean that she was necessarily right, nor that she looked much beyond vision when considering how features might be bound together into perceptual objects. While such a narrow focus undoubtedly makes sense, given the complexity of human multisensory information processing, it is nevertheless somewhat surprising to find that Treisman herself never extended her feature integration theory outside of the visual modality. After all, she first cut her ‘attentional teeth’ thinking about problems of auditory and audiovisual selective attention. In this article, we review the literature concerning feature integration beyond the visual modality, concentrating, in particular, on the integration of features from different sensory modalities. We highlight a number of the challenges, as far as any straightforward attempt to extend feature integration to the non-visual (i.e. auditory and tactile) and cross-modal (or multisensory) cases, is concerned. These challenges include the problem of how basic features should be defined, the question of whether it even makes sense to talk of objects of perception in the auditory and olfactory modalities, the possibility of integration outside of the focus of spatial attention, and the integration of features from different sensory modalities in the control of action. Nevertheless, despite such limitations, Treisman’s feature integration theory still stands as the standard approach against which alternatives are assessed, be it in the visual case or, increasingly, beyond.